Effects of different wet distillers’ grains ratios on fermentation quality, nitrogen fractions and bacterial communities of total mixed ration silage - Ermei Du; Ning Mao; Shihao Liu; Hanyu Zhang; Meiling Fan; Hong Sun; Yulong Zheng; Qiming Cheng; Chunmei Wang; Ping Li; Yixiao Xie (BMC Microbiology)
Abstract Objective Wet distiller’s grains (WDG) are rich in crude protein, yet challenging to preserve. Nevertheless, incorporating WDG into total mixed ration (TMR) silage holds promise for enhancing fermentation quality. This study investigated the effects of varying WDG proportions on nitrogen composition, fermentation quality, and microorganisms in TMR silage. Methods Three TMR formulations were prepared: (1) 0% WDG (T0), (2) 15% WDG (T15), and (3) 30% WDG (T30) were ensiled for 7, 15, 30 and 60 days. Results After 7 days of ensiling, butyric acid was detected in T0 and T15 groups, while T30 exhibited significantly lower levels (p < 0.05). Both T15 and T30 treatments led to improved V-scores of TMR silage. Non-protein nitrogen (NPN) production was slower in T30, with significant increases observed in NPN levels for T0 and T15 after 30 days (p < 0.05). However, the abundance of Clostridium was extremely low in the present study. Protein degradation and and butyric acid production may be attributed to Weissella. Conclusion The fermentation quality of TMR silage is always decreasing during storage, so its storage time should be minimized. Incorporating 30% WDG reduced abundance of Weissella, resulting in less protein degradation and better fermentation quality in TMR silage.